ML-13 The primary treatment outcomes and future problems of PCNSL elderly patients in our institute. (28th November 2020) - Kambe, Atsushi; Amisaki, Hidefumi; Kuwamoto, Yuhei; Shimizu, Tsuyoshi; Nakajima, Sadao; Torihashi, Koichi; Uno, Tetsuji; Sakamoto, Makoto; Kurosaki, Masamichi
Abstract: Background and purpose: Since the introduction of HD-MTX, cognitive symptoms after irradiation have become a problem mainly in elderly patients. In this study, we evaluated the treatment outcomes of over 70 years old PCNSL patients after HD-MTX introduction. Subjects and methods: From April 2009 to December 2019, there were 46 cases of PCNSL patients who had been treated in our institute. The HD-MTX treatment group had 42 cases and the R-MPV-A treatment group had 4 cases. In the HD-MTX treatment group, 30–40 Gy of whole brain irradiation was performed (n=32), but cases of SRS or no irradiation (n=10) were included due to poor PS. The R-MPV-A treatment group was performed with whole brain 23.4 Gy + local 21.6 Gy or no irradiation. The remission rate and outcome (mOS) were examined. Results: The background of all 46 patients was 28 males and 18 females, with an average age of 75.8 years (70–87 years). The pathological diagnosis was DLBCL in all cases. The remission rate after chemotherapy in the HD-MTX treatment group was 52.4% (22/42). The post-irradiation remission rate was 78.6% in cases of whole-brain irradiation (n=14) among non-remission cases (n=20). The mOS of the whole-brain irradiation cases was 58.5 months (n=18) in the remission cases (n=22), but was 38.7 months (n=14) in the non-remission cases (n=20). The mOS of patients with SRS or no irradiation (n=10) was 12.4 months. The R-MPV-A treatment group (n=4) had a remission rate of 100% after chemotherapy. Of the 26 cases whose cause of death could be identified in the HD-MTX treatment group, 58% (15/26) had tumor-related death and 30% (8/26) had pneumonia or suffocation. Conclusion: R-MPV-A has a high remission rate even in elderly patients, and if the irradiation dose can be reduced or avoided with R-MPV-A, ADL maintenance will be expected in elderly patients.